Local behaviour of the derivative of a mid point cubic spline interpolator - H. P. Dikshit; S. S. Rana (International Journal of Mathematics and Mathematical Sciences)
In the present paper, we obtain an asymptotically precise estimate for the derivative of the difference between the cubic spline interpolating at the mid points of a uniform partition and the function interpolated.